Characteristics of Foamed Concrete Containing Ultra-fine Drift Sand of the Yangtze River - Fares Ali Al-Sairafi; Chaohua Jiang; Wang XinXin; Hussein Yousif Aziz (Civil Engineering Journal, 2022)
The primary goal of this study was to evaluate the use of Ultra-fine Drift Sand from the Yangtze River (China) in place of natural sand in the production of foamed concrete. The experimental design included factors with varying levels: the proportion of Ultra-fine Drift Sand at four levels (0 percent, 30%, 60%, and 100%). Ultra-fine Drift Sand was substituted in proportion to the mass of material. Each factor's effect on compressive strength, density (dry and saturated), air voids, and water absorption was assessed. According to the results, all factors had significant findings. The compressive strength of concrete increased due to an increase in curing time; fly ash content up to 30%; increasing the percent of Yangzi river sand; and decreasing slag. The mixture of 10% SF (Silica Fume), 24% FA (Fly Ash) and 100% YS (Yangzi soil) gives the enhanced results in concrete strength, by which it reaches about 7 MPa compared with other findings. The remaining percentages of mixing benefit compression strength results. This method of treatment provides an economical way through providing a cheap material that enhances the mechanical properties of concrete, provides a light weight concrete, and a good isolator material to improve the building's thermal insulation to reduce ecological problems and save energy. Doi: 10.28991/CEJ-2022-08-08-013 Full Text: PDF